Advancing precision medicine in gliomas through single-cell sequencing: unveiling the complex tumor microenvironment - Li, Jinwei; Zhang, Yang; Liang, Cong; Yan, Xianlei; Hui, Xuhui; Liu, Quan (Frontiers in Cell and Developmental Biology, 2024)
Glioblastoma (GBM) displays an infiltrative growth characteristic that recruits neighboring normal cells to facilitate tumor growth, maintenance, and invasion into the brain. While the blood-brain barrier serves as a critical natural defense mechanism for the central nervous system, GBM disrupts this barrier, resulting in the infiltration of macrophages from the peripheral bone marrow and the activation of resident microglia.Recent advancements in single-cell transcriptomics and spatial transcriptomics have refined the categorization of cells within the tumor microenvironment for precise identification. The intricate interactions and influences on cell growth within the tumor microenvironment under multi-omics conditions are succinctly outlined. The factors and mechanisms involving microglia, macrophages, endothelial cells, and T cells that